Online System for Change Faculty and Program of UNIMAS. - MOHD DANISH, AL HASAN (Universiti Malaysia Sarawak (UNIMAS), 2020)
The Online System for Change Faculty and Program of UNIMAS helps the student submit their form in a short time without going to the faculty. This paper represents the design of the proposed system by using Lucidchart and Mockflow Wireframe online tools. The proposed system plays a vital role by ensure the student detail go to the database after been approve by current and receiving faculty. This system also assists the officer of faculty to track the recent applicant or past applicant. The applicant can know their current status by login to the system and click the “status” button for more detail.